[Mn(dien)2]MnSnS4, [Mn(1, 2-dap)]2Sn2S6 and [Mn(en)2]MnGeS4: from 1D anionic and neutral chains to 3D neutral frameworks. Issue 4 (3rd December 2014) - Yue, Cheng-Yang; Lei, Xiao-Wu; Yin, Ling; Zhai, Xiu-Rong; Ba, Zhong-Ren; Niu, Yan-Qiang; Li, Yue-Peng
Abstract : Three new organic–inorganic hybrid manganese thiogermanates and thiostannates with 1D anionic or neutral chains and 3D neutral frameworks have been synthesized and feature interesting antiferromagnetic or ferromagnetic properties. Abstract : Three new organic–inorganic hybrid manganese thiogermanates and thiostannates, namely, [Mn(en)2 ]MnGeS4 (1, en = ethylenediamine), [Mn(dien)2 ]MnSnS4 (2, dien = diethylenetriamine) and [Mn(1, 2-dap)]2 Sn2 S6 (3, 1, 2-dap = 1, 2-diaminopropane), have been solvothermally synthesized and structurally characterized. Compound1 has a three-dimensional (3D) neutral framework composed of one-dimensional (1D) [MnGeS4 ] 2− chains and unsaturated [Mn(en)2 ] 2+ cations interconnected via Mn–S bonds, whereas compounds2–3 feature 1D [MnSnS4 ] 2− anionic chains and 1D neutral [Mn(1, 2-dap)]2 Sn2 S6 chains, respectively. Investigation into the magnetic properties of the title compounds reveals antiferromagnetic and ferromagnetic coupling interactions between the Mn(ii ) ions for compounds1 and3, respectively. The optical and luminescence properties, as well as the thermal stabilities, were also studied.